Peran Komunikasi Interpersonal dan Dialog Kinerja terhadap Kinerja Tim: Systematic Literature Review - Mentari Putriwulan; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
This research analyzes the role of interpersonal communication and performance dialogue on team performance. In an organizational context, effective interpersonal communication plays an important role to enhance cooperation, collaboration, and problem-solving among team members, which in turn affects overall team performance. Weak communication can lead to misunderstandings, hinder collaboration, and reduce team effectiveness. Performance dialog, which involves structured discussions between leaders and team members, also plays an important role in monitoring and improving team performance. Research shows that regularly conducted performance dialogues can clarify goals, improve coordination, and strengthen relationships between team members. This research uses a qualitative method with a literature study approach, reviewing various journals related to interpersonal communication, performance dialog, and team performance. The results show that both, effective interpersonal communication and structured performance dialogue, strongly positively influence team performance. Therefore, organizations need to develop communication skills and support performance dialogue as part of a more effective team management strategy.